Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1756-0500-6-355
|View full text |Cite
|
Sign up to set email alerts
|

Timely access and quality of care in colorectal cancer: a population-based cohort study using administrative data

Abstract: BackgroundWhile efforts to improve cancer outcomes have typically focused on improving quality of care, recently, a growing emphasis has been placed on timely access to quality cancer care. This retrospective cohort study examines, at a population level, the relationship between quality and timeliness of colorectal cancer (CRC) care in a single Canadian province (Nova Scotia). Through the provincial cancer registry, we identified all residents diagnosed with invasive CRC between 2001 and 2005 that underwent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…The two studies used similar methods to ours, however, an important difference is that we excluded urgent patients from the calculation of the diagnostic interval whereas the other two did not. If we include urgent patients, the median diagnostic interval was 55 days in our study with 37% of all patients diagnosed within 4 weeks, similar to 37.1% found by Porter et al [34]. A multicenter US study that included mainly male patients of Veteran Affairs hospitals reported a median diagnostic interval of 91 days for screen-detected and 74 days for symptom-detected CRC [33].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The two studies used similar methods to ours, however, an important difference is that we excluded urgent patients from the calculation of the diagnostic interval whereas the other two did not. If we include urgent patients, the median diagnostic interval was 55 days in our study with 37% of all patients diagnosed within 4 weeks, similar to 37.1% found by Porter et al [34]. A multicenter US study that included mainly male patients of Veteran Affairs hospitals reported a median diagnostic interval of 91 days for screen-detected and 74 days for symptom-detected CRC [33].…”
Section: Discussionsupporting
confidence: 84%
“…Two other population-based studies conducted in Canada that included slightly older patient cohorts, diagnosed in years 2001–2005, reported a median diagnostic interval of 44–64 days (depending on year of diagnosis) [12] and 44 days [34]. The two studies used similar methods to ours, however, an important difference is that we excluded urgent patients from the calculation of the diagnostic interval whereas the other two did not.…”
Section: Discussionmentioning
confidence: 94%
“…Perhaps unsurprisingly, and as noted by others, findings from previous studies have been mixed (41). While in our study rural patients with colorectal cancer had a longer time from presentation to diagnosis and treatment (diagnostic and health system interval), Scottish and French studies found no such association (17,42) and a Canadian study found the opposite-rural patients had greater odds of being diagnosed within four weeks compared with urban patients (43). Some studies report longer intervals for rural patients than we found, such as longer median patient and diagnostic intervals in Western Australia (11), and treatment interval for rural colon cancer patients in Ontario (19).…”
Section: Discussionsupporting
confidence: 54%
“…However, there may be disadvantages of rapid diagnosis or treatment commencement; Canadian studies show that patients with colorectal cancer who waited longer for diagnosis or treatment more often received higher-quality healthcare. 41 42 While we were unable to measure clinical aspects of quality of care, these findings indicate that relationships between timeliness, utilisation and care quality are complex.…”
Section: Discussionmentioning
confidence: 90%